Thylakoid Localized Type 2 NAD(P)H Dehydrogenase NdbA Optimizes Light-Activated Heterotrophic Growth of Synechocystis sp. PCC 6803 - Tuomas Huokko; Dorota Muth-Pawlak; Eva-Mari Aro (NLM (Medline), 2022)
NdbA, one of the three type 2 NAD(P)H dehydrogenases (NDH-2) in Synechocystis sp. PCC 6803 (hereafter Synechocystis) was here localized to the thylakoid membrane (TM), unique for the three NDH-2s, and investigated with respect to photosynthetic and cellular redox metabolism. For this purpose, a deletion mutant (ΔndbA) and a complementation strain overexpressing NdbA (ΔndbA::ndbA) were constructed. It is demonstrated that NdbA is expressed at very low level in the wild-type (WT) Synechocystis under photoautotrophic (PA) growth whilst substantially higher expression occurs under light-activated heterotrophic growth (LAHG). The absence of NdbA resulted in non-optimal growth of Synechocystis under LAHG and concomitantly enhanced the expression of photoprotection-related flavodiiron proteins and carbon acquisition-related proteins as well as various transporters, but downregulated a few iron homeostasis-related proteins. NdbA overexpression, on the other hand, promoted photosynthetic pigmentation and functionality of photosystem I under LAHG conditions while distinct photoprotective and carbon concentrating proteins were downregulated. NdbA overexpression also exerted an effect on the expression of many signaling and gene regulation proteins. It is concluded that the amount and function of NdbA in the TM has a capacity to modulate the redox signaling of gene expression, but apparently has a major physiological role in maintaining iron homeostasis under LAHG conditions. LC-MS/MS data are available via ProteomeXchange with identifier PXD011671.